SYSTEM OF PROVIDING WAGES TO THE WELFARE OF THE PRESPECTIVE WORKERS OF IBN HAZM - Aula Izatul Aini; Komarudin A; Umi Robiatul Ngijah (ICO EDUSHA, 2021)
A person's goal is to earn income, which will later be used to achieve needs. Yayasan Mukhtar Syafa’at employs construction workers to build infrastructure facilities in supporting learning. The purpose of this study was the first to know the system of wages of construction workers applied at the Yayasan Mukhtar Syafa'at Blokagung of Banyuwangi Regency Both views of Ibn Hazm about the wage system provided by the Foundation to the welfare of construction workers in the Yayasan Mukhtar Syafa'at. The research method used in this research is to use this type of qualitative research through a case study approach. The data analysis tool used in this study was using the Interactive Milles and Huberman Models. The results of this study are the first that the Yayasan Mukhtar Syafa'at in providing workers' wages there are two types of divisions, the first part for builders and secondly for building porters and the one used is the term wage system. The welfare of construction workers has also been fulfilled based on Ibn Hazm's opinion of one's prosperity, it is seen from the main needs fulfilled and the education of children fulfilled. The conclusion of this study is that the system used by the Yayasan Mukhtar Syafa’at is in accordance with the study of existing theories and about the welfare of workers is also in accordance with Ibn Hazm's theory that the Yayasan Mukhtar Syafa’at in addition to providing wages also provides social security. In addition, the welfare of construction workers has also been proven by the fulfillment of children's education. Keyword: System of Providing Wages, welfare Ibnu Hazm References AB, S. (2017). Benang-Benang Merah Teori Kesejahteraan Sosial. Makassar, Maret. Aini, A. I., & Niha, A. (2021). Impulse Buying Behavior Santri Perspektif Maslahah Imam Al-Ghazali. Jurnal Darussalam: Jurnal Pendidikan, Komunikasi Dan Pemikiran Hukum Islam, 12(1), 17–33. Chamid, N. (2010). Jejak langkah sejarah pemikiran ekonomi Islam. Handoko, T. H. (2016). Manajemen personalia dan sumberdaya manusia. BPFE. Himayah, M. A., & Alkaf, H. (2001). Ibnu Hazm wa Minhajuh fi dirasah al-Adyan. PT Lentera Basritama. Hm, M. S. (2016). Pemikiran Fikih Ekonomi Ibnu Hazm tentang Kesejahteraan Tenaga Kerja. IQTISHADIA: Jurnal Ekonomi Dan Perbankan Syariah, 3(2), 199–234. Huda, N. (2015). Ekonomi Pembangunan Islam cetakan ke-1. Kencana. Jakarta. Indonesia, D. A. R. (1989). al-Qur’an dan Terjemahnya. Surabaya: Mahkota. Indonesia, P. R. (1992). Undang-Undang Republik Indonesia Nomor 3 Tahun 1992 tentang Jaminan Sosial Tenaga Kerja. Jakarta: Sekretariat Negara. Nasrun, H. (2007). Fiqh Muamalah. Gaya Media Pratama, Jakarta. Yin, R. K. (2008). Studi kasus: Desain & metode. Zainal, V. R., Basalamah, S., & Muhammad, N. (2014). Islamic Human Capital Management. Jakarta: PT Rajagrafindo Persada.